Resveratrol in Alzheimer's disease: a review of pathophysiology and therapeutic potential - SOUSA, Júlia Canto e; SANTANA, Ana Carolina Fauaze; MAGALHÃES, Gabriela Jesus Prado (Arquivos de Neuro-Psiquiatria, 2020)
Background: Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by progressive and irreversible loss of cognitive function. The presence of senile plaques is one of the pathological markers of the disease and is associated with the onset of neuroinflammatory mechanisms. The exact pathophysiology of AD has not been completely understood, and there are no curative therapies yet. Resveratrol (3,5,4'-trihydroxy-trans-stilbene) is a polyphenol that is noted for its antioxidant and anti-inflammatory properties. Objective: To review the role of resveratrol in the pathophysiological aspects of AD. Methods: This study carried out a literature review using PubMed/Medline, Virtual Health Library (VHL), Web of Sciences, SCOPUS and the Cochrane Library databases. Original research articles, describing both in vitro and in vivo experiments, published between 2008 and 2018, were included. Results: We identified 667 articles, of which 619 were excluded because they were repeated or did not follow the inclusion criteria. The present study includes the remaining 48 articles. Discussion: Resveratrol demonstrates beneficial and protective effects in AD models and seems to provide a promising therapeutic alternative. Conclusion: Although resveratrol appears to mitigate some pathophysiological aspects of AD, further studies are needed to prove the safety and efficacy of this compound in humans.
Keywords: amyloid; sirtuin 1; antioxidants; polyphenols; nutraceuticals